High‐Performance Noncovalently Fused‐Ring Electron Acceptors for Organic Solar Cells Enabled by Noncovalent Intramolecular Interactions and End‐Group Engineering. (20th April 2021) - Zhang, Xin; Qin, Linqing; Yu, Jianwei; Li, Yuhao; Wei, Yanan; Liu, Xingzheng; Lu, Xinhui; Gao, Feng; Huang, Hui
Abstract: Noncovalently fused‐ring electron acceptors (NFREAs) have attracted much attention in recent years owing to their advantages of simple synthetic routes, high yields and low costs. However, the efficiencies of NFREAs based organic solar cells (OSCs) are still far behind those of fused‐ring electron acceptors (FREAs). Herein, a series of NFREAs with S⋅⋅⋅O noncovalent intramolecular interactions were designed and synthesized with a two‐step synthetic route. Upon introducing π‐extended end‐groups into the backbones, the electronic properties, charge transport, film morphology, and energy loss were precisely tuned by fine‐tuning the degree of multi‐fluorination. As a result, a record PCE of 14.53 % in labs and a certified PCE of 13.8 % for NFREAs based devices were obtained. This contribution demonstrated that combining the strategies of noncovalent conformational locks and π‐extended end‐group engineering is a simple and effective way to explore high‐performance NFREAs. Abstract : We constructed a series of noncovalently fused‐ring electron acceptors (NFREAs) with S⋅⋅⋅O noncovalent intramolecular interactions. Combining the strategies of noncovalent conformational locks and π‐extended end‐group engineering, a record PCE of 14.53 % in labs and a certified PCE of 13.8 % for NFREAs based devices were achieved.